Faktor – Faktor Yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pada PTN-BH - Khaeril Anwar Junaedi; Syamsu Alam; Mursalim Nohong (Hasanuddin Journal of Business Strategy, 2019)
Financial statements are a major tool used as a measurement tool to assess the performance of profit-oriented institutions (profit-oriented) and non-profit institutions (not profit-oriented). Hasanuddin University is part of a non-profit institution that has an interest in having quality financial reports. This research aims to find out the factors that influence the quality of financial statement information at Hasanuddin University. The method used in this study is a quantitative research method that has a level of associative explanation. The population in this study is all financial management employees who work in the finance department of the 3rd Floor of the Rectorate of Hasanuddin University. While the sample selection uses the total sampling method with a total sample of 62 people. The results of this study are of the four variables namely human resource competency, technology utilization, leadership support, and funding support which have the most significant influence, namely human resource competence, then successive variables of financial support, leadership support, and technology utilization variables. The competency of human resources is very influential on the quality of the financial statements of Hasanuddin University. The better the competence of human resources, the better the quality of the financial statement of Hasanuddin University. So it is important to increase the knowledge of human resources about processing financial statements and to provide training in accordance with what is needed.